KENYAMANAN TERMAL ADAPTIF MAHASISWA DI UNIVERSITAS SAINS DAN TEKNOLOGI JAYAPURA - Zulfiana, Indah Sari (Jurnal Teknologi Terpadu, 2021)
To get good quality learning, a comfortable study room is needed both visually, audally and thermally. Thermal comfort is greatly influenced by the climatic conditions of a region. In areas with high daily air temperature, high humidity and low air velocity, it is difficult to produce thermal comfort with natural air conditioning. Jayapura City is one of the cities in Indonesia with daily air temperature and high humidity and low air velocity. Therefore, adaptive processes are needed to achieve thermal comfort in spaces, including study rooms. Each human's adaptive thermal comfort is different according to local climatic conditions. The purpose of this study was to determine the adaptive thermal comfort of students in naturally ventilated classrooms at the Jayapura University of Science and Technology (USTJ) in the city of Jayapura, Papua, namely students 'neutrality, acceptance and thermal preferences, as well as students' adaptive behavior in achieving thermal comfort. This research was conducted in one of USTJ's classrooms in Jayapura, Papua. Four environmental parameters were measured, namely temperature, humidity, wind speed, and mean radiant temperature (MRT). The data were obtained through filling out a questionnaire to 100 USTJ students during the space measurement. Thermal neutrality data were analyzed using regression analysis using SPSS software, while thermal acceptance and preference and adaptive behavior were analyzed based on the results of the questionnaire answers. The results showed that USTJ students' thermal neutrality was at 29.Â°C Ta or 29.55Â°C Top. all students can accept the thermal conditions of the room, but 59% of students choose to want the room to be cooler due to their thermal preferences. The adaptive behavior that is carried out is turning on the fan, picking up objects to be used as a fan, leaving the room and drinking more often.